The values of Islamic education in the Gumbrekan tradition - Sari, Septian Kurnia; Astuti, Efi Tri (ATTARBIYAH: Journal of Islamic Culture and Education, 2023)
The aim of this research is to examine in depth what values of Islamic education are contained in the Gumbrekan traditional rituals carried out by the people of Pringkuku Village, Pringkuku District, and Pacitan Regency. This research uses a qualitative method with a descriptive approach. The data collection techniques used were observation, interviews, and a literature study. data analysis technique by examining the Gumbrekan tradition as a whole and in depth. Then interpret the data obtained and draw conclusions from it. The results of the research show that the values of Islamic education found in the Gumbrekan tradition consist of: (1) the value of Tauhid (belief); (2) worship value; (3) moral values; and (4) community values. Gumbrekan has undergone many role changes. Even though it is related to one place and another, the Gumbrekan Tradition, which was originally sacred, has undergone many changes with the introduction of Islamic values, which refer to eradicating actions that lead to shirk.